Visualization of subthalamic nucleus on susceptibility weighted imaging and the verification of accuracy by microelectrode recording - Yu, Kaijia; Yao, Qi; Wu, Yuanyang; Li, Jianyu; Shen, Lihua; Gu, Xiaosu; Jia, Zhongzheng; Zhang, Jiajia; Shen, Jianhong (Frontiers in Human Neuroscience, 2025)
ObjectiveTo investigate the advantages of susceptibility weighted imaging (SWI) for visualizing the subthalamic nucleus (STN) and to verify the accuracy of this method by microelectrode recordings (MERs) and deep brain stimulation (DBS).MethodsWe included 42 patients with Parkinson’s disease who underwent STN-DBS in our center. The bilateral STN (n = 84) was visualized on preoperative 3-T T2-weighted imaging (T2w) and SWI and compared using a 4-point scale. The contrast-to-noise ratio of STN was calculated and compared between two images. The dorsoventral borders of the STN on SWI and T2w were measured and compared using data recorded by intraoperative MERs.ResultsThe visualization scores for the STN and contrast-to-noise ratio of STN relative to the zona incerta and substantia nigra were significantly higher on SWI than on T2w images (p < 0.05). There was no significant difference in the location of the dorsal and ventral borders of the STN visualized by SWI when compared with MER data (p > 0.05). Errors for the dorsal and ventral borders of SWI-STN, as verified by MER (0.56 ± 0.32 mm and 0.72 ± 0.33 mm, respectively) were significantly lower than errors on T2w (0.75 ± 0.33 mm and 0.82 ± 0.45 mm for the dorsal and ventral borders, respectively) (p < 0.05).Conclusion3-T SWI was a superior method for delineating the STN than conventional T2w. When applying this method, the dorsoventral SWI-STN border coincided reliably with the physiological border determined by MERs. Direct targeting of the STN using SWI can help optimize preoperative target localization, trajectory planning, and postoperative programming.